The impact of the Brumadinho dam failure in Naô Xohâ village - Silva, Adriana Aparecida; Lunas, Divina Aparecida Leonel; Bicalho, Poliene Soares dos Santos; Maciel, Roseli Martins Tristão (Sustainability in Debate, 2019)
It is still under strong impact from the Brumadinho dam failure that this article was written. Our main goal is to approach, in the midst of so many social groups hit by this announced tragedy, the reality of the village Naô Xohã, whose population lives on the banks of the Paraopeba River, also victimized by this environmental disaster of consequences not yet dimensioned. As it is a contemporary theme, several press releases were used to compose the narrative, as well as to build a comprehensive review of the literature on the Movement of People Affected by Dams and on socioeconomic and environmental impacts. The proposition, however, is based on an interdisciplinary approach to the theme, which is the impact of the Brumadinho dam failure in Naô Xohã village, mainly due to the pollution that spread over the Paraopeba River. To this end, a fruitful dialogue was established between history, geography, economics and environmental issues.